Characterisation of clinical isolates of oxacillin-susceptible mecA-positive Staphylococcus aureus in China from 2009 to 2014. (December 2017) - Song, Yunjia; Cui, Lanqing; Lv, Yuan; Li, Yun; Xue, Feng
Highlights: 34 oxacillin-susceptible mecA -positive S. aureus (OS-MRSA) clinical isolates were found. ST338/59-t437-SCC mec V (47%; 16/34) was the predominant clone. Most OS-MRSA were susceptible to most antimicrobials except macrolides, clindamycin and chloramphenicol. Oxacillin is inadequate to identify all mec -positive MRSA; cefoxitin is more appropriate. Abstract: Objectives: The aim of this study was to investigate the prevalence and molecular characteristics of clinical oxacillin-susceptible mecA -positive Staphylococcus aureus (OS-MRSA) isolates in China from July 2009 to June 2014. Methods: A total of 2068 non-duplicate S. aureus isolates were collected from 21 hospitals. Antimicrobial susceptibility testing was performed by the agar dilution method. All OS-MRSA strains were screened for the presence of the genes mecA, mecC and nuc as well as the Panton–Valentine leukocidin gene ( pvl ). Staphylococcal cassette chromosome mec (SCC mec ) typing, staphylococcal protein A ( spa ) typing and multilocus sequence typing (MLST) were performed to analyse the isolate genotypes. Results: A total of 34 S. aureus isolates were mecA- positive but were susceptible to oxacillin [minimum inhibitory concentration (MIC) ≤ 2 mg/L]. All OS-MRSA isolates were resistant to cefoxitin and most were also multiresistant to other antibiotics besides β-lactams. Among the 34 OS-MRSA isolates, nine spa and three SCC mec types were detected and, combined with MLST, ST338/59-t437-SCC mec V (47%; 16/34) was the predominant clone. In addition, 17 strains (50%) carried the pvl gene. Conclusions: The most frequent clone of OS-MRSA isolates in China was ST338-t437-SCC mec V. Most of the OS-MRSA isolates were susceptible to the majority of antibacterial agents except macrolides, clindamycin and chloramphenicol.